Chionanthus chrysopetalus (Oleaceae), a New Species from Peru - Lombardi, Julio Antonio (Phytotaxa, 2017)
Chionanthus is a genus from the plant family Oleaceae that is characterized by the presence of small calyces, 4-lobed corollas with petals arranged in pairs and held together by the filament bases, less commonly with a very short tube, two stamens in most species, and drupaceous fruits. As part of ongoing taxonomic studies of the Neotropical Oleaceae, we detected an undescribed species from Peru, that is here described and illustrated. Chionanthus chrysopetalus Cornejo ex Lombardi resembles C. implicatus and C. compactus, two species from northwestern South America, by the elliptic leaves. However, C. chrysopetalus can be separated by both taxa by the hispidulous indument, and yellow corollas, unusual features within the genus. In this study, I present a detailed description for the new taxon, notes on the phenology, geographic distribution, habitat, conservation status, and etymology.